Platelet-Like Gold Nanostars for Cancer Therapy: The Ability to Treat Cancer and Evade Immune Reactions - Kim, Min Woo; Lee, Gibok; Niidome, Takuro; Komohara, Yoshihiro; Lee, Ruda; Park, Yong Il (Frontiers in Bioengineering and Biotechnology, 2020)
The cell membrane-coating strategy has opened new opportunities for the development of biomimetic and multifunctional drug delivery platforms. Recently, a variety of gold nanoparticles, which can combine with blood cell membranes, have been shown to provide an effective approach for cancer therapy. Meanwhile, this class of hybrid nanostructures can deceive the immunological system to exhibit synergistic therapeutic effects. Here, we synthesized red blood cell (RBC) and platelet membrane-coated gold nanostars containing curcumin (R/P-cGNS) and evaluated whether R/P-cGNS had improved anticancer efficacy. We also validated a controlled release profile under near-infrared irradiation for the ability to target melanoma cells and to have an immunomodulatory effect on macrophages. RBC membrane coating provided self-antigens; therefore, it could evade clearance by macrophages, while platelet membrane coating provided targetability to cancer cells. Additionally, the nutraceutical curcumin provided anticancer and anti-inflammatory effects. In conclusion, the results presented in this study demonstrated that R/P-cGNS can deliver drugs to the target region and enhance anticancer effects while avoiding macrophage phagocytosis. We believe that R/P-cGNS can be a new design of the cell-based hybrid system for effective cancer therapy.